High energy density Na-metal batteries enabled by a tailored carbonate-based electrolyte - Chen, Jiawei; Peng, Yu; Yin, Yue; Liu, Mingzhu; Fang, Zhong; Xie, Yihua; Chen, Bowen; Cao, Yongjie; Xing, Lidan; Huang, Jianhang; Wang, Yonggang; Dong, Xiaoli; et al. (Energy & environmental science, 2022)
High-voltage sodium metal batteries (SMBs) offer a viable way toward high energy densities. However, they synchronously place severe demands on the electrolyte for the notorious reactivity of Na-metal and the catalytic nature of aggressive high-voltage chemistries. Here, we fabricate a tailored carbonate-based electrolyte involving lithium difluorobis(oxalato) phosphate (LiDFBOP) as a multifunctional additive, where DFBOP − anions can generate stable and robust interphases on both the anode and cathode. Meanwhile, Li + -ions can take part in the solvation structure to regulate the electrolyte stability as well as resist dendritic deposition via electrostatic shielding. Such optimization effectively realizes high coulombic efficiency (98.6%) and prolonged life (2600 h) of Na plating/stripping together with the upgraded reversibility of the Na 3 V 2 (PO 4 ) 2 F 3 cathode. Moreover, the assembled 4.5 V Na||Na 3 V 2 (PO 4 ) 2 F 3 SMB achieves impressive cycling stability with 90% capacity retention after 220 cycles and a high energy density of 295 W h kg −1 with limited Na. The proposed electrolyte strategy can shed light on further optimization for high-energy sodium metal chemistries. A carbonate-based electrolyte is well-designed via a multifunctional lithium difluorobis(oxalato) phosphate (LiDFBOP) additive, endowing 4.5 V sodium metal batteries with high energy density, excellent cycling stability and a wide temperature range.